Improving Reading Achievement on Descriptive Texts Using Choral Reading Strategy - Lenny Ita Marbun; Gaya Tridinanti; Heru Setiawan (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2024)
Teachers can employ flexible grouping to enhance choral and duet reading which can benefit students' fluency and expressiveness. This strategy enrichment the students of reading boosts confidence in their ability to speak and read English. This research aimed to determine whether there was a significant difference in reading achievement on the descriptive text between tenth-grade students at SMK Gajah Mada 3 Palembang who were taught using the choral reading approach and those who were not. The participants were tenth-grade students from SMK Gajah Mada 3 Palembang. This research sample consisted of 41 students chosen using a purposive selection technique. They were placed into two groups: experimental and control groups. This research used a quasi-experimental design. The data collection tool was a reading achievement test administered twice to the sample (pretest and posttest). There were 20 valid multiple-choice questions. The data were not normally distributed; thus, the Mann-Whitney U Test and the Wilcoxon Signed Rank Test were employed to examine data. According to the Wilcoxon Signed Rank test findings, the students' reading achievement significantly improved when they used the choral reading strategy. The Mann-Whitney U test results demonstrated students who got a treatment utilizing the choral reading technique excelled in reading compared to those who did not. There was a substantial difference in reading achievement on descriptive text between tenth-grade students at SMK Gajah Mada 3 Palembang who were taught using choral reading strategies and those who were not.